Peningkatan Keterampilan Berkarya Tari Melalui Model Pembelajaran Kooperatif STAD Berbasis Stimulus Kinestetik (Penelitian Tindakan Kelas Pada Kelas VIII B SMP Negeri 6 Kota Tangerang) - Shabrina Dwi Hany; Elindra Yetti; Ojang Cahyadi (Jurnal Pendidikan Tari, 2025)
The low dance creation skills are caused by the lack of experience in the dance creation process, which makes students feel less confident in developing their dance works. This causes students of SMP Negeri 6 Kota Tangerang to get low scores in dance practice. This study aims to describe the application of the STAD cooperative learning model based on kinesthetic stimuli to improve the dance creation skills of 36 students in class VIII-B. The application of the STAD model is carried out in heterogeneous groups with individual value taking. This study is included in the type of classroom action research (PTK). This action research uses the Kemmis and McTaggart model. The results of the study showed an increase in dance creation skills in students, which was proven by the average student score of 49 increasing to 58 in cycle I, then reaching 73 in cycle II. This shows that the STAD model can improve dance creation skills in class VIII-B students of SMP Negeri 6 Kota Tangerang.